Kajian Elemen Interior Berdasarkan Vitruvius pada Gereja Bethany Indonesia cabang Manyar di Surabaya - Kirawan, Veliana (Intra, 2015)
One of the churches that chosen to be a subject of interior space research study is Bethany Indonesia Church Manyar branch in Surabaya which is the pioneer of Bethany Indonesia Church in Surabaya. The chosen research methodology is a descriptive methodology with a case study describing the detailed picture of interior in Bethany Indonesia Church Manyar branch Surabaya. This research focuses on the application of interior elements according to Vitruvius in the worship place in Bethany Indonesia Church Manyar branch Surabaya which is beauty (venustatis), durability (firmatis), and the usability/functionality (utilitas) that become the interior system because including the entirety of interior. The researched interior design study includes layout, elements in interior. The findings of the research shows that function as a requirement to fulfill the creation of specific space atmosphere and in the aim has been applied in this church except in the security aspect. Whereas the durability aspect as the interior power that can be reviewed from the material use also applied well even though some minor weaknesses still exist, furthermore the venustatis aspect which includes the design elements such as line, shape, color and texture have been applied well and result in a dynamic, strong and balance impression, but if it relates to the design principal such as proportion, unity, harmony and focal point, not all have been applied well in Bethany Indonesia Church Manyar branch.